2021
DOI: 10.36941/jesr-2021-0130
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Impact on Children with Autism Spectrum Disorder and Intellectual Disability: Study in Saudi Arabia

Abstract: This study investigated the impact of COVID-19 on children with autism spectrum disorder and intellectually disabled children from a parent's point of view and statistically significant differences between the responses of parents of children with disabilities about the impacts of the COVID-19 attributed to the child’s sex (male/female), the type of the child’s disability (autism/intellectual disability), the parents’ education level (intermediate or lower/above intermediate). The study used the quantitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Concerns about child development without proper service support or access to specialist therapeutic services emerged as the highest source of psychological distress for families of children and young people with ASD 50,80 . One study noted that parents who reported regression in their child's skills due to service loss, felt a helplessness when trying to provide intervention to their children with ASD and learning disability 81 . The study recommended involving parents of children with disabilities in therapy so that they gained the skills to maintain therapy in a future crisis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns about child development without proper service support or access to specialist therapeutic services emerged as the highest source of psychological distress for families of children and young people with ASD 50,80 . One study noted that parents who reported regression in their child's skills due to service loss, felt a helplessness when trying to provide intervention to their children with ASD and learning disability 81 . The study recommended involving parents of children with disabilities in therapy so that they gained the skills to maintain therapy in a future crisis.…”
Section: Resultsmentioning
confidence: 99%
“…50,80 One study noted that parents who reported regression in their child's skills due to service loss, felt a helplessness when trying to provide intervention to their children with ASD and learning disability. 81 The study recommended involving parents of children with disabilities in therapy so that they gained the skills to maintain therapy in a future crisis.…”
Section: Frequency Of Consultationsmentioning
confidence: 99%
“…A report from Botswana argued that the benefits of protection and control measures from COVID-19 should be made available to all ( Samboma, 2021 ). Moreover, a study in Saudi Arabia focused on the impact of COVID-19 on children with ASDs and IDs and recommended enhanced rehabilitation sessions ( Athbah, 2021 ). However, studies on people with IDs have generally been limited to Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…The study results of Theis et al (2021) showed that COVID-19 caused imposing unprecedented restrictions on the weakest social groups, including people with intellectual disabilities, as 61% of the sample suffered from a decrease in their physical activity due to curfew, and the psychological health of 90% of the sample of people with intellectual disability was negatively affected. Additionally, Athbah's (2021) study that was carried out on a sample of children with intellectual disabilities proved a great influence of COVID-19 on them, as all rehabilitation processes stopped giving room for undesirable procedures of behavior modification, which led to a detrimental impact of the psychological aspects.…”
Section: Introductionmentioning
confidence: 99%